A educação em Direitos Humanos nos projetos político-pedagógicos das escolas de São Paulo - Klein, Ana Maria [UNESP]; D'Água, Solange Lima [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2015)
The article presents data from a qualitative study that aimed to investigate the presence of aspects that integrate knowledge, values and practice of the Human Rights Education (HRE) in the political-pedagogical projects (PPPs) of public schools in the state of São Paulo. 15 documents were analyzed from criteria based on reference documents for HRE in Brazil. The criteria were organized into seven areas: internal and external community; principles and concepts of education; goals; curriculum; democratic participation and school environment; teacher training and evaluation. We sought to identify whether the HRE related elements were missing, or if they were just mentioned or stood out through propositional planned actions in PPPs. The data demonstrate that the contents directly related to HRE are absent from PPPs, some issues related to this type of education are weakly mentioned and there are some planned actions that promote rights. However, the intentional, systematic and conscious planning of HRE is not yet reflected in this document type.

O artigo traz os dados de uma pesquisa qualitativa que teve por objetivo levantar, por meio da análise dos Projetos Político-Pedagógicos (PPPs), a presença de elementos que integram conhecimentos, valores e práticas da Educação em Direitos Humanos (EDH) nas escolas públicas do estado de São Paulo. Foram analisados 15 documentos a partir de critérios estabelecidos com base em documentos-referência para a EDH no país. Os critérios foram organizados em sete âmbitos: comunidade interna e externa; princípios e concepções de educação; objetivos; currículo; participação democrática e ambiente escolar; formação docente e avaliação. Buscou-se identificar se elementos relacionados à EDH estavam ausentes, se eram apenas mencionados ou se destacavam de maneira propositiva, por meio de ações planejadas nos PPPs. Os dados demonstram que os conteúdos diretamente relacionados à EDH estão ausentes dos PPPs, algumas temáticas relacionadas a este tipo de educação são fracamente mencionadas e há ações planejadas pelas escolas que promovem direitos, no entanto, o planejamento intencional, sistematizado e consciente da EDH ainda não se reflete neste tipo de documento.
Human Rights education in political-pedagogical projects of São Paulo's schools
Keywords: Human Rights Education; political-pedagogical project; schools.; Educação em Direitos Humanos; Projeto Político-Pedagógico; escolas.